Production of energy-storage paper electrodes using a pilot-scale paper machine. Issue 40 (27th September 2022) - Isacsson, Patrik; Jain, Karishma; Fall, Andreas; Chauve, Valerie; Hajian, Alireza; Granberg, Hjalmar; Boiron, Lucie; Berggren, Magnus; Håkansson, Karl; Edberg, Jesper; Engquist, Isak; Wågberg, Lars
Abstract : Rolls of supercapacitor electrodes have successfully been produced on a pilot paper machine with a novel material concept. Abstract : The global efforts in electrifying our society drive the demand for low-cost and sustainable energy storage solutions. In the present work, a novel material concept was investigated to enable fabrication of several 10 meter-long rolls of supercapacitor paper electrodes on a pilot-scale paper machine. The material concept was based on cationized, cellulose-rich wood-derived fibres, conducting polymer PEDOT:PSS, and activated carbon filler particles. Cationic fibres saturated with anionic PEDOT:PSS provide a conducting scaffold hosting the activated carbon, which functions as the active charge-storage material. The response from further additives was systematically investigated for several critical paper properties. Cellulose nanofibrils were found to improve mechanical properties, while carbon black enhanced both the conductivity and the storage capacity of the activated carbon, reaching a specific capacitance of 67 F g −1 . This pilot trial shows that "classical" papermaking methods are fit for the purpose and provides valuable insights on how to further advance bio-based energy storage solutions for large-scale applications.